Fuel Characteristics of Thermal Power Station as Index of Its Thermal Efficiency - A. E. Piir; V. B. Kuntysh (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
It is proposed to calculate values of specific consumptions of conventional fuel for generating heat and electric power in a combined electrical installation (Thermal Power Station) on the basis of a thermal and dynamic approach or an exergetic balance of a turbine plant. It is shown that a fuel characteristic of Thermal Power Station is an objective index of a thermal electrical installation